Exploring legitimization strategies for contested uses of citizen-generated data for policy - Sven Schade; Yashuhito Abe; Anna Berti Suman (Edward Elgar Publishing, 2021)
In this article, we investigate how citizens use data they gather as a rhetorical resource for demanding environmental policy interventions and advancing environmental justice claims. While producing citizen-generated data (CGD) can be regarded as a form of ‘social protest’, citizens and interested institutional actors still have to ‘justify’ the role of lay people in producing data on environmental issues. Such actors adopt a variety of arguments to persuade public authorities to recognize CGD as a legitimate resource for policy making and regulation. So far, scant attention has been devoted to inspecting the different legitimization strategies adopted to push for institutional use of CGD. In order to fill this knowledge gap, we examine which distinctive strategies are adopted by interested actors: existing legitimization arguments are clustered, and strategies are outlined, based on a literature review and exemplary cases. We explore the conceivable effects of these strategies on targeted policy uses. Two threads emerge from the research, entailing two complementary arguments: namely that listening to CGD is a governmental obligation and that including CGD is ultimately beneficial for making environmental decisions. We conclude that the most used strategies include showing the scientific strength and contributory potential of CGD, whereas environmental rights and democracy-based strategies are still rare. We discuss why we consider this result to be problematic and outline a future research agenda.